Ultralow Thermal Conductivity, Multiband Electronic Structure and High Thermoelectric Figure of Merit in TlCuSe - Lin, Wenwen; He, Jiangang; Su, Xianli; Zhang, Xiaomi; Xia, Yi; Bailey, Trevor P.; Stoumpos, Constantinos C.; Tan, Ganjian; Rettie, Alexander J. E.; Chung, Duck Young; Dravid, Vinayak P.; Uher, Ctirad; et al. (Advanced materials (Weinheim), 2021)
The entanglement of lattice thermal conductivity, electrical conductivity, and Seebeck coefficient complicates the process of optimizing thermoelectric performance in most thermoelectric materials. Semiconductors with ultralow lattice thermal conductivities and high power factors at the same time are scarce but fundamentally interesting and practically important for energy conversion. Herein, an intrinsic p‐type semiconductor TlCuSe that has an intrinsically ultralow thermal conductivity (0.25 W m−1 K−1), a high power factor (11.6 µW cm−1 K−2), and a high figure of merit, ZT (1.9) at 643 K is described. The weak chemical bonds, originating from the filled antibonding orbitals p‐d* within the edge‐sharing CuSe4 tetrahedra and long TlSe bonds in the PbClF‐type structure, in conjunction with the large atomic mass of Tl lead to an ultralow sound velocity. Strong anharmonicity, coming from Tl+ lone‐pair electrons, boosts phonon–phonon scattering rates and further suppresses lattice thermal conductivity. The multiband character of the valence band structure contributing to power factor enhancement benefits from the lone‐pair electrons of Tl+ as well, which modify the orbital character of the valence bands, and pushes the valence band maximum off the Γ‐point, increasing the band degeneracy. The results provide new insight on the rational design of thermoelectric materials. Semiconductors with ultralow lattice thermal conductivities and high power factors at the same time are scarce but fundamentally interesting in understanding thermoelectric energy conversion. TlCuSe exhibiting intrinsically ultralow thermal conductivity (0.25 W m–1 K–1), a high power factor (11.6 μW cm–1 K–1), and a high figure of merit ZT (1.9) at 643 K is described.